Integrasi Nasional dan Hak Azasi Manusia - Riza Noer Arfani (Jurnal Ilmu Sosial dan Ilmu Politik, 2001)
This article is an effort to explore conceptual relations of national integration as an endeavor toward nation-building and issues related to human rights promotion. Aspects of national integration which might impede effort of human rights protection are examined. These include area of issues as broad as territory, socio-cultural, and world view in the nation-building endeavor. Questions on what kind of preconditions and criteria should be established in the settlement of territory of a nation-state, what kind of socio-cultural conditions should be developed in order to unite a nation-state, and what kind of paradigm should be founded to create and develop shared beliefs, ideas and views of a nation-state are among the one shall be addressed in the article. Finally, it is also inevitable to look at the arrangement of normative logics in world order system, if we are to explore human rights promotion in the wake of (nation-) state sovereignty.